2003
DOI: 10.1097/01.ccm.0000054869.21603.9a
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different airway management strategies to ventilate apneic, nonpreoxygenated patients

Abstract: Paramedics were able to employ the laryngeal mask airway, Combitube, and cuffed oropharyngeal airway in apneic patients with normal lung compliance and airways. In this population, bag-valve-mask ventilation was the most simple and successful strategy. Small tidal volumes applied with a pediatric self-inflating bag and 100% oxygen resulted in adequate oxygenation and ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 21 publications
3
40
1
3
Order By: Relevance
“…The advantages of the esophageal-tracheal tube over the endotracheal tube are related chiefly to ease of training. 12,43 Ventilation and oxygenation with the esophageal-tracheal tube compare favorably with those achieved with the endotracheal tube. 44 In several controlled clinical trials involving both inhospital and out-of-hospital resuscitation of adults, providers with all levels of experience were able to insert the esophageal-tracheal tube and deliver ventilation comparable to that achieved with endotracheal intubation.…”
Section: Esophageal-tracheal Tubementioning
confidence: 96%
See 3 more Smart Citations
“…The advantages of the esophageal-tracheal tube over the endotracheal tube are related chiefly to ease of training. 12,43 Ventilation and oxygenation with the esophageal-tracheal tube compare favorably with those achieved with the endotracheal tube. 44 In several controlled clinical trials involving both inhospital and out-of-hospital resuscitation of adults, providers with all levels of experience were able to insert the esophageal-tracheal tube and deliver ventilation comparable to that achieved with endotracheal intubation.…”
Section: Esophageal-tracheal Tubementioning
confidence: 96%
“…12,39,44,55,[62][63][64][65] After successful insertion, a small proportion of patients cannot be ventilated with the laryngeal mask airway. 12,44,55 With this in mind, it is important for providers to have an alternative strategy for airway management. Providers who insert the laryngeal mask airway should receive adequate initial training and then should practice insertion of the device regularly.…”
Section: Laryngeal Mask Airwaymentioning
confidence: 99%
See 2 more Smart Citations
“…quency or time of replacement), 3,4,8,[10][11][12][13][14][15][16][17][18][19][20]26 (2) 11 The present study demonstrated the current status of LMA and BVM with regard to ABG in cases of out-of-hospital cardiac arrest. Although there are a few reports comparing blood gas data during CPR with LMA and BVM, this is the first to show the data of "out-of hospital" cardiac arrests with "VF/VT" on initial ECG at the scene as classified by the Utstein template.…”
Section: Discussionmentioning
confidence: 99%